Analisis Kinerja dan Tingkat Pelayanan Ruas Jalan Raya Ciomas Kreteg Kabupaten Bogor - Hutama, Vigie Priantika Putra (Publica Scientific Solution, 2024)
The development of transportation has an impact on increasing traffic flow. The increase in the number of vehicles and high levels of human movement will cause congestion if it is not balanced with adequate road infrastructure. The aim of the research is to identify the level of service and performance of road sections. Methodology is a method or technique used to test the validity of using certain research. The research location is on Jalan Raya Ciomas Kreteg, Bogor Regency because it is a residential and commercial area so it is busy every day. Data collection techniques are taken through surveys of geometric conditions, traffic flow, speed and side obstacles. The supporting data is obtained from the population according to the Central Statistics Agency. The survey was carried out during rush hour and it was discovered that the traffic volume was 1216.75 pcu / hour. The analysis results show that the capacity of Jalan Raya Ciomas Kreteg is 2201.45 pcu / hour and DS is 0.55, so the Jalan Raya Ciomas Kreteg section is in class C in the classification of road service levels.